Polymer alloy and preparation method and application thereof
By using specific types of phosphorus-based flame retardants, anti-irror agitator and filler in PC/ABS alloy materials, a polymer alloy with low smoke density, excellent humidity and heat resistance and good noise resistance is formed, which solves the shortcomings of existing materials in moisture and heat aging and noise resistance.
Patent Information
- Application Number
- CN202411878737.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing PC/ABS alloy materials have shortcomings in humidity and heat aging performance and anti-sound performance, which are difficult to meet the needs of high-temperature and high-humidity environments such as new energy vehicles.
A composite method of 60 to 80 parts of polycarbonate, 8 to 20 parts of acrylonitrile-butadiene-styrene copolymer, 5 to 12 parts of phosphorus-based flame retardant, 1 to 6 parts of anti-isodic additives and 0.8 to 5 parts of fillers was used to form a polymer alloy with low smoke density, excellent moisture and heat resistance and good anti-isodic effect.
The polymer alloy has achieved low smoke density, excellent moisture and heat aging resistance and good anti-irror noise effect. At the same time, the material is free of halogen, and has the characteristics of low odor and low emanation.
Smart Images

Figure BDA0005197622960000091 
Figure BDA0005197622960000092 
Figure BDA0005197622960000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a polymer alloy and a preparation method and application thereof. Background Art
[0002] Polycarbonate (PC) is an engineering plastic with high impact and high heat resistance, but it has high melt viscosity, is difficult to process, and is sensitive to notches. Acrylonitrile-butadiene-styrene (ABS) resin is a thermoplastic polymer material with high strength, high toughness, and easy processing, but it has poor thermal stability. By combining the two, the advantages of the two resins can be combined and the disadvantages of both can be overcome to obtain PC / ABS alloy materials with excellent performance, which can be widely used in various fields, especially in the automotive field.
[0003] At present, many interior parts of automobiles need to use PC / ABS alloy materials. The smoke density of automobile interiors is generally required to be ≤75. As automobiles represented by BYD and Yutong begin to electrify and "go overseas" to hot and humid regions such as Africa, South America, and Southeast Asia, in order to adapt to the local high temperature and high humidity natural environment, higher requirements are put forward for the wet and hot aging performance of interior materials. At the same time, after the electrification of new energy vehicles, the background noise of the engine has dropped rapidly, and the "abnormal sound problem" caused by the assembly and extrusion of interior parts is particularly prominent. Therefore, the traditional automobile interior PC / ABS alloy materials also need to be upgraded accordingly to deal with the abnormal sound problem.
[0004] Patents CN105431486A and CN105209312A use polycarbonate and polycarbonate siloxane copolymers with special isophthalic structures to prepare halogen-free flame-retardant composite materials by adding bisphenol A bis(diphenyl phosphate) (BDP), polyetherimide (PEI), etc., and can obtain materials with low smoke density. For example, patent CN102604315A discloses a low smoke density PC / ABS alloy for automotive interior parts. The low smoke density PC / ABS alloy is compounded with four flame retardants and smoke suppressants such as zinc borate, molybdenum trioxide, ammonium octamolybdate and zinc molybdate, which can effectively reduce the smoke density of the PC / ABS alloy. However, the moisture and heat aging resistance and abnormal noise resistance of the PC / ABS alloy materials disclosed in the aforementioned patents need to be further improved.
[0005] Therefore, developing a halogen-free polymer alloy material with low smoke density, excellent resistance to moisture and heat aging, and resistance to abnormal noise is an urgent problem to be solved in this field. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention aims to provide a polymer alloy and its preparation method and application. The polymer alloy has excellent resistance to moisture and heat aging, low smoke density and good anti-sound effect, and the polymer has no halogen addition and has the characteristics of low odor and low emission.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In the first aspect, the present invention provides a polymer alloy, which comprises, by weight, 60 to 80 parts of polycarbonate, 8 to 20 parts of acrylonitrile-butadiene-styrene copolymer, 5 to 12 parts of phosphorus-based flame retardants, 1 to 6 parts of anti-noise aids and 0.8 to 5 parts of fillers; the phosphorus-based flame retardant comprises a phosphazene flame retardant; the filler comprises talcum powder; the anti-noise aid comprises maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer.
[0009] In the present invention, by adopting a specific type of phosphorus flame retardant, an anti-sounding auxiliary agent and a filler compound, it is beneficial to improve the moisture-heat aging resistance of the PC / ABS polymer alloy, reduce its smoke density, and also make the polymer alloy have an anti-sounding effect.
[0010] In the present invention, 60 to 80 parts of polycarbonate can be, for example, 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts or a range consisting of any of the above values; preferably 62 to 78 parts, more preferably 65 to 75 parts.
[0011] In the present invention, 8 to 20 parts of acrylonitrile-butadiene-styrene copolymer can be, for example, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts, 10.5 parts, 11 parts, 11.5 parts, 12 parts, 12.5 parts, 13 parts, 13.5 parts, 14 parts, 14.5 parts, 15 parts, 15.5 parts, 16 parts, 16.5 parts, 17 parts, 17.5 parts, 18 parts, 18.5 parts, 19 parts, 19.5 parts, 20 parts or a range consisting of any of the above values; preferably, it is 10 to 19.5 parts, and more preferably, it is 12 to 18 parts.
[0012] In the present invention, 5 to 12 parts of phosphorus flame retardant can be, for example, 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, 6 parts, 6.2 parts, 6.4 parts, 6.6 parts, 6.8 parts, 7 parts, 7.2 parts, 7.4 parts, 7.6 parts, 7.8 parts, 8 parts, 8.2 parts, 8.4 parts, 8.6 parts, 8.8 parts, 9 parts, 9.2 parts, 9.4 parts, 9.6 parts, 9.8 parts, 10 parts, 10.2 parts, 10.4 parts, 10.6 parts, 10.8 parts, 11 parts, 11.2 parts, 11.4 parts, 11.6 parts, 11.8 parts, 12 parts or the range composed of any of the above values; preferably 6.5 to 10.5 parts, more preferably 7.5 to 9.5 parts.
[0013] In the present invention, 1 to 6 parts of anti-sound aids can be, for example, 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, 6 parts or a range consisting of any of the above values; preferably 1.2 to 5.5 parts, more preferably 1.5 to 4.5 parts.
[0014] In the present invention, 0.8 to 5 parts of filler can be, for example, 0.8 parts, 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5 parts or a range consisting of any of the above values; preferably 1 to 3 parts, more preferably 2 to 2.6 parts.
[0015] In the present invention, the grafting rate of the maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer is 0.5-2%, for example, it can be 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, etc.; the test method of the grafting rate includes acid-base titration method.
[0016] Preferably, the phosphazene flame retardant comprises a cyclic phosphazene compound.
[0017] Preferably, the cyclic phosphazene compound accounts for 60-100% of the total mass of the phosphazene flame retardant, for example, it can be 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, 100% and the like.
[0018] Preferably, the cyclic phosphazene compound comprises compound A and / or compound B; compound A comprises hexaphenoxy cyclotriphosphazene; compound B comprises at least one of hexa(4-hydroxymethylphenoxy)cyclotriphosphazene, hexa(4-aminophenoxy)cyclotriphosphazene, hexa(p-carboxyphenoxy)cyclotriphosphazene or tri(p-phenylenedioxy)cyclophosphazene, more preferably compound B comprises at least one of hexa(4-hydroxymethylphenoxy)cyclotriphosphazene, hexa(4-aminophenoxy)cyclotriphosphazene or hexa(p-carboxyphenoxy)cyclotriphosphazene.
[0019] Preferably, the cyclic phosphazene compound comprises compound A and compound B, and the mass ratio of compound A to compound B is (0.4-3.6):1, wherein the specific value in (0.4-3.6) can be, for example, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6 or a range consisting of any of the above values; further preferably, it is (1-3):1, and more preferably, it is (1.4-2.6):1.
[0020] Preferably, the anti-sound additive further comprises ultra-high molecular weight polyethylene.
[0021] Preferably, the anti-noise aid comprises maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer and ultra-high molecular weight polyethylene, and the mass ratio of the maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer and the ultra-high molecular weight polyethylene is 1:(0.1~0.9), wherein the specific value in (0.1~0.9) can be, for example, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9 or a range composed of any of the above values; more preferably 1:(0.3~0.6).
[0022] Preferably, the average particle size of the talc is 1 to 10 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm or a range consisting of any of the above values; more preferably, 3 to 8 μm; more preferably, 4 to 6 μm.
[0023] Preferably, the filler further includes a second filler, and the second filler includes boron nitride and / or silicon nitride.
[0024] In the present invention, the average particle size of the second filler is 4 to 15 μm, for example, it can be 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or a range consisting of any of the above values.
[0025] In the present invention, the average particle sizes of the talcum powder and the second filler can be tested by light scattering method.
[0026] Preferably, the filler includes talcum powder and a second filler, and the mass ratio of the talcum powder to the second filler is 1:(0.2-0.8), wherein the specific value in (0.2-0.8) can be, for example, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8 and the range consisting of any of the above values; more preferably 1:(0.35-0.55).
[0027] Preferably, the polymer alloy further includes 2 to 5 parts of a toughening agent in parts by weight, for example, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4 parts, 4.2 parts, 4.5 parts, 4.8 parts, 5 parts or a range consisting of any of the above values; more preferably, 3.5 to 4.5 parts.
[0028] Preferably, the toughening agent comprises maleic anhydride grafted acrylonitrile-butadiene-styrene copolymer and / or methyl methacrylate-butadiene-styrene copolymer.
[0029] Preferably, the polymer alloy further includes, by weight, 0.2 to 1 parts of an antioxidant (for example, 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts or any range consisting of the above values) and / or 0.2 to 1 parts of a lubricant (for example, 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts or any range consisting of the above values).
[0030] Preferably, the antioxidant includes at least one of a hindered phenol antioxidant, a thioester antioxidant, a phosphite antioxidant or a hindered amine antioxidant.
[0031] Preferably, the lubricant includes at least one of magnesium stearate, pentaerythritol stearate, ethylene bisstearamide or polyethylene wax.
[0032] In the present invention, the polycarbonate may be bisphenol A polycarbonate; the polycarbonate may be a polycarbonate produced by a phosgene method, and the polycarbonate produced by a phosgene method may be commercially available; according to standard ISO 1133-1:2022, the test conditions are 300°C, 1.2kg, and the melt index of the polycarbonate is 8 to 12g / 10min, for example, 8g / 10min, 8.5g / 10min, 9g / 10min, 9.5g / 10min, 10g / 10min, 10.5g / 10min, 11g / 10min, 11.5g / 10min, 12g / 10min or a range consisting of any of the above values.
[0033] In the present invention, the mass percentage of polycarbonate in the polymer alloy is ≥60%, for example, it can be 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, 90% or any range between the above values; more preferably, the mass percentage of polycarbonate is ≥65%.
[0034] In the present invention, the acrylonitrile-butadiene-styrene copolymer may be an acrylonitrile-butadiene-styrene copolymer produced by a bulk process, and the acrylonitrile-butadiene-styrene copolymer produced by the bulk process may be commercially available; according to standard ISO 1133-1:2022, the test conditions are 220° C., 10 kg, and the melt index of the acrylonitrile-butadiene-styrene copolymer is 15 to 25 g / 10 min, for example, 15 g / 10 min, 16 g / 10 min, 17 g / 10 min, 18 g / 10 min, 19 g / 10 min, 20 g / 10 min, 21 g / 10 min, 22 g / 10 min, 23 g / 10 min, 24 g / 10 min, 25 g / 10 min or a range consisting of any of the above numerical values.
[0035] As a preferred technical solution of the present invention, the polymer alloy includes, by weight, 65 to 75 parts of polycarbonate, 12 to 18 parts of acrylonitrile-butadiene-styrene copolymer, 6.5 to 10.5 parts of phosphorus-based flame retardant, 1.8 to 4.5 parts of anti-sound additive, 1 to 3 parts of filler, 2 to 5 parts of toughening agent, 0.2 to 1 part of antioxidant and 0.2 to 1 part of lubricant.
[0036] In a second aspect, the present invention provides a method for preparing the polymer alloy according to the first aspect, the preparation method comprising the following steps:
[0037] The polymer alloy is obtained by mixing polycarbonate, acrylonitrile-butadiene-styrene copolymer, phosphorus-based flame retardant, anti-squeak auxiliary agent and filler, and extruding.
[0038] Preferably, the mixed material further comprises at least one of a toughening agent, an antioxidant or a lubricant.
[0039] Preferably, the extrusion temperature is 180-280°C.
[0040] In the present invention, the extrusion is carried out in a twin-screw extruder, which is a co-rotating twin-screw extruder, the aspect ratio of the screw is 25-48, and the screw barrel is provided with a vacuum pumping device and a temperature control device; wherein the vacuum degree is -0.08 to -0.1 MPa, the temperature of the feeding and conveying section is 190-220°C, the temperature of the core plasticizing section is 240-260°C, the temperature of the post-homogenizing extrusion section is 260-270°C, and the screw speed is 400-600rpm.
[0041] In the present invention, the extrusion further includes the steps of cooling, drying and pelletizing.
[0042] In a third aspect, the present invention provides an automobile interior material, wherein the automobile interior material comprises the polymer alloy according to the first aspect.
[0043] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] The polymer alloy provided by the present invention adopts a specific type of phosphorus-based flame retardant, an anti-sounding auxiliary agent and a filler compound, so that the PC / ABS polymer alloy can have excellent resistance to moisture and heat aging, low smoke density and good anti-sounding effect, and the material is environmentally friendly. DETAILED DESCRIPTION
[0046] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0047] The materials used in the present invention can be purchased from the market or prepared by conventional methods; unless otherwise specified, the materials used in the present invention are as follows:
[0048] PC resin: Japan Mitsubishi S-2000F.
[0049] ABS resin: Takahashi Petrochemical ABS 8434.
[0050] Flame retardants: hexaphenoxy cyclotriphosphazene, hexa(4-hydroxymethylphenoxy)cyclotriphosphazene, tri(phenylenedioxy)cyclophosphazene, bisphenol A bis(diphenyl phosphate) are all commercially available.
[0051] Anti-sound additives: maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer (MAH-g-SEBS, Kraton FG1901, maleic anhydride grafting rate 1.5%); ultra-high molecular weight polyethylene (UHMWPE, Japan Mitsui Chemicals UHMWPE-540RU); styrene-hydrogenated ethylene-styrene copolymer, American Kraton 1152.
[0052] filler:
[0053] Talc 1: D50 particle size is 4.25 μm, Liaoning Xinda SDC-9489;
[0054] Talc 2: D50 particle size is 5.5-6.0 μm, SD-8072 from Liaoning Xinda Talc Group Co., Ltd.;
[0055] Talc 3: Grind talc 1 to a D50 particle size of 1.5 μm;
[0056] Talc 4: D50 particle size is 9-11 μm, SD-9012 from Liaoning Xinda Talc Group Co., Ltd.
[0057] Silicon nitride: D50 particle size is 5 μm, purchased from Beijing Xingrongyuan Technology Co., Ltd.
[0058] Toughening agent: maleic anhydride grafted acrylonitrile-butadiene-styrene copolymer (MAH-g-ABS, Shenyang Ketong KT-2), methyl methacrylate-butadiene-styrene copolymer (MBS, Rohm and Haas 2620).
[0059] Lubricant: Pentaerythritol stearate, LOXIOL P 861 / 3.5 from Koning, Germany.
[0060] Antioxidant: a mixture of BASF antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) and antioxidant 168 (tris[2,4-di-tert-butylphenyl] phosphite) in a mass ratio of 1:1.
[0061] Examples 1 to 24, Comparative Examples 1 to 7
[0062] Embodiments 1 to 24 and comparative examples 1 to 7 respectively provide a polymer alloy, and the formula of the polymer alloy is shown in Table 1 in parts by weight; wherein, “ / ” indicates that the component is not included in the formula; the preparation method of the polymer alloy comprises: mixing PC resin, ABS resin, toughening agent, phosphorus flame retardant, anti-noise aid, filler, antioxidant and lubricant, and adding the mixture into the main barrel of a twin-screw extruder (screw diameter is 35 mm, aspect ratio L / D=48) for extrusion, wherein the temperature of each section of the main barrel (from the feed port to the die outlet) is controlled to be 190°C, 240°C, 250°C, 260°C, 260°C, 265°C, 270°C, respectively, and the twin screw speed is 500rpm; cooling, drying and pelletizing the extruded material to obtain the polymer alloy.
[0063] Table 1
[0064]
[0065] Table 2
[0066]
[0067]
[0068] Table 3
[0069]
[0070] Table 4
[0071]
[0072]
[0073] Table 5
[0074]
[0075] Performance Testing
[0076] The polymer alloys provided in Examples 1 to 24 and Comparative Examples 1 to 7 were dried in a blast oven at 100°C for 4 hours and then injection molded into standard specimens and sample plates using an injection molding machine. The molded specimens were placed in an environment of 50±5% relative humidity and 23±2°C for at least 24 hours and then subjected to the following performance tests.
[0077] (1) Simple supported beam notch impact strength test: According to ISO179-2010 standard, injection molding A-type notch, the test condition is tested at room temperature.
[0078] (2) Vicat softening temperature: according to B in ISO 306-2013 50 Method for testing.
[0079] (3) Anti-sound test: Test the risk factor (RPN) of abnormal sound according to standard VDA230-206-2005.
[0080] (4) Smoke density: Tested in accordance with GB / T 8627-2007.
[0081] (5) Moisture and heat aging resistance test: The injection molded specimens (ISO 1A tensile specimens) were aged at a temperature of 85°C and a humidity of 85% for 1000 h, and the tensile strength of the specimens before and after aging was tested according to standard ISO 527-1:2019. The tensile performance retention rate was calculated, and the tensile performance retention rate = tensile strength after aging / tensile strength before aging × 100%.
[0082] The specific test results are shown in Table 6.
[0083] Table 6
[0084]
[0085]
[0086] As shown in Table 6, the polymer alloy provided by the present invention adopts a specific type of phosphorus flame retardant, an anti-sounding additive and a filler compound, so that the PC / ABS polymer alloy can have excellent resistance to wet heat aging, low smoke density and good anti-sounding effect, and the simply supported beam notched impact strength of the polymer alloy is greater than 49KJ / m 2 , Vicat softening temperature>105℃, RPN value<6, smoke density<61, aging for 1000h at temperature of 85℃ and humidity of 85%, tensile performance retention rate>94%.
[0087] It can be seen from Comparative Examples 1 to 3 that without a specific type of phosphorus-based flame retardant, anti-sounding aid or filler compound, the polymer alloy has a high smoke density, poor anti-sounding effect and poor aging resistance.
[0088] It can be seen from Comparative Examples 4 to 6 that if one of the phosphorus-based flame retardant, the anti-sounding aid and the filler is missing, the polymer alloy has a high smoke density, a poor anti-sounding effect and poor aging resistance.
[0089] It can be seen from Comparative Example 7 that PC and ABS are not compounded in a specific ratio, the polymer alloy has a low simply supported beam notched impact strength, poor aging resistance, poor anti-abnormal noise effect, and increased smoke density.
[0090] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A polymer alloy, characterized in that In parts by weight, the polymer alloy comprises 60 to 80 parts of polycarbonate, 8 to 20 parts of acrylonitrile-butadiene-styrene copolymer, 5 to 12 parts of phosphorus-based flame retardant, 1 to 6 parts of anti-sounding additive and 0.8 to 5 parts of filler; The phosphorus-based flame retardant includes a phosphazene flame retardant; The filler includes talc; The anti-sounding auxiliary agent includes maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer.
2. The polymer alloy according to claim 1, characterized in that The phosphazene flame retardant includes a cyclic phosphazene compound; Preferably, the cyclic phosphazene compound comprises compound A and / or compound B; The compound A comprises hexaphenoxy cyclotriphosphazene; The compound B comprises at least one of hexa(4-hydroxymethylphenoxy)cyclotriphosphazene, hexa(4-aminophenoxy)cyclotriphosphazene, hexa(p-carboxyphenoxy)cyclotriphosphazene or tri(p-phenylenedioxy)cyclophosphazene, more preferably compound B comprises at least one of hexa(4-hydroxymethylphenoxy)cyclotriphosphazene, hexa(4-aminophenoxy)cyclotriphosphazene or hexa(p-carboxyphenoxy)cyclotriphosphazene; Preferably, the cyclic phosphazene compound comprises compound A and compound B, and the mass ratio of compound A to compound B is (0.4-3.6):1, more preferably (1.4-2.6):
1.
3. The polymer alloy according to claim 1 or 2, characterized in that The anti-sounding auxiliary agent also includes ultra-high molecular weight polyethylene; Preferably, the anti-noise aid comprises maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer and ultra-high molecular weight polyethylene, and the mass ratio of the maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer to the ultra-high molecular weight polyethylene is 1:(0.1~0.9), and more preferably 1:(0.3~0.6).
4. The polymer alloy according to any one of claims 1 to 3, characterized in that The average particle size of the talc powder is 1 to 10 μm, preferably 3 to 8 μm; Preferably, the filler further comprises a second filler, and the second filler comprises boron nitride and / or silicon nitride; Preferably, the filler includes talc powder and a second filler, and the mass ratio of the talc powder to the second filler is 1:(0.2-0.8), more preferably 1:(0.35-0.55).
5. The polymer alloy according to any one of claims 1 to 4, characterized in that The polymer alloy further comprises 2 to 5 parts of a toughening agent in parts by weight; Preferably, the toughening agent comprises maleic anhydride grafted acrylonitrile-butadiene-styrene copolymer and / or methyl methacrylate-butadiene-styrene copolymer.
6. The polymer alloy according to any one of claims 1 to 5, characterized in that The polymer alloy further comprises, by weight, 0.2 to 1 part of an antioxidant and / or 0.2 to 1 part of a lubricant; Preferably, the antioxidant comprises at least one of a hindered phenol antioxidant, a thioester antioxidant, a phosphite antioxidant or a hindered amine antioxidant; Preferably, the lubricant includes at least one of magnesium stearate, pentaerythritol stearate, ethylene bisstearamide or polyethylene wax.
7. The polymer alloy according to any one of claims 1 to 6, characterized in that In parts by weight, the polymer alloy includes 65 to 75 parts of polycarbonate, 12 to 18 parts of acrylonitrile-butadiene-styrene copolymer, 6.5 to 10.5 parts of phosphorus-based flame retardant, 1.8 to 4.5 parts of anti-sound additive, 1 to 3 parts of filler, 2 to 5 parts of toughening agent, 0.2 to 1 part of antioxidant and 0.2 to 1 part of lubricant.
8. A method for preparing a polymer alloy according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The polymer alloy is obtained by mixing polycarbonate, acrylonitrile-butadiene-styrene copolymer, phosphorus-based flame retardant, anti-squeak auxiliary agent and filler, and extruding.
9. The preparation method according to claim 8, characterized in that: The mixed material further includes at least one of a toughening agent, an antioxidant or a lubricant; Preferably, the extrusion temperature is 180-280°C.
10. An automobile interior material, characterized in that: The automobile interior material comprises the polymer alloy according to any one of claims 1 to 7.
Citation Information
Patent Citations
Low-smoke-density PC / ABS (Poly Carbonate / Acrylonitrile Butadiene Styrene) plastic for automobile interior and preparation method thereof
CN102604315A
Interior train components having low smoke and low heat release, and methods of their manufacture
CN105209312A
Interior train components having low smoke and low heat release, and methods of their manufacture
CN105431486A
Flame retardant polycarbonate compositions, methods of manufacture thereof and articles comprising the same
CN104334638A
Low-precipitation high-filling high-modulus flame-retardant PC (polycarbonate) / ABS (acrylonitrile-butadiene-styrene grafted copolymer) composition
CN105885378A
Cited By
Flame-retardant brazing paste as well as preparation method and brazing process thereof
CN121820949A
A fire-retardant soldering paste, a preparation method thereof and a soldering process
CN121820949B